Going local : decentralization and the promise of good governance - Grindle, Merilee Serrill (Princeton University Press, 2009)
Many developing countries have a history of highly centralized governments. Since the late 1980s, a large number of these governments have introduced decentralization to increase democracy and improve services, especially in small communities far from capital cities. In Going Local, an unprecedented study of the effects of decentralization on thirty Mexican municipalities, Merilee Grindle describes how local governments respond when they are assigned new responsibilities and resources under decentralization policies. She explains why decentralization leads to better local governments in some c.